Investigation of pressure effect on methane conversions incatalytic combustion system - Sharol Azri, Halim (2008)
Catalytic Converter is a device to clean up the exhaust gases by breaking down the harmful gas compounds. When the engine burns fuel, it produces gases that pollute the air such as hydrocarbons, carbon monoxide and nitrogen oxides. This project is carried out to investigate the influences of reactor pressure on the methane conversion and to find the effect of reverse flow on methane conversion. The single channel has been considered as a part of a monolith structure and from the modeling point of view only one channel needs to be investigated, assuming that symmetry holds for the inlet conditions. The single channel reactor is a cylindrical tube with diameter 2 mm and length 20 mm. Computational fluids dynamic (CFD) analysis simulate the reaction of burned methane with oxygen and show the graphical result of path line the reaction flow from the inlet to the exhaust. From the graph the simulation has show that the optimum pressure for the methane conversion rate is at 1 atm pressure. The Reverse flow that develops near the outlet of channel when the reactor pressure reach at 5 atm slightly increase the conversion rate of burned methane.